Mediación en Espacios Virtuales Inmersivos - Piña Lobos, Luis Alberto (Universidad Santiago de Cali, 2020)
Getting to know us today has other nuances very different from yesteryear times; to know something or to know a anyplace somewhere we used to use books, stories, print paper versions or grandmother ́s stories to shape distant spaces, places or things that we did not fully understand, we came to assume many things; today technology does not open a door to the world instead it opens a great gate show even more things, more stories and culture that in a life-time we ́ve could had not know. The issues is how to mediate knowledge and new ways of communicating in a globalized world that points out to individuality, how to make that an advantage to improve it and endow it with a holistic and complex view for the harmony of living beings that inhabit this planet for now.